Ameliorative Effects of Vitamin E against Ceftriaxone-induced Adverse Effects in Broilers Challenged with E. coli - Ghandour, Marwa; Shams, Gamal A.; Hassan, Heba M.; Ali, Amira M.; Baz, Heba A. (Journal of Advanced Veterinary Research, 2023)
Ceftriaxone is a broad spectrum antimicrobial that commonly used in chicken farms for the purpose of the control of avian bacterial diseases. However, the use of ceftriaxone can be associated with some adverse effects. This study examined vitamin E’s protective properties against ceftriaxone-induced histopathological, inflammatory, and oxidative damage in broiler chickens challenged with E. coli. When broiler chicks are exposed to E. coli O78, colibacillosis was developed. The sickened birds displayed a variety of general clinical symptoms. Ceftriaxone was used as a treatment and could lower morbidity and fatality rates to 10% and 4%, respectively. The use of ceftriaxone was associated with the occurrence of some histopathological lesions. In addition, either E. coli or ceftriaxone could cause alterations in erythrogram, antioxidant status, and induction of inflammatory markers. Interestingly, the use of vitamin E with ceftriaxone could markedly improve the histopathological alterations and upregulate the antioxidant status and reduce the release of the inflammatory markers. In conclusion, the present study’s findings showed that ceftriaxone is a powerful antibacterial drug, especially when used to treat E. coli in broilers. Vitamin E is strongly advised for usage in broilers to minimize ceftriaxone-induced adverse effects.Â